2021
DOI: 10.3390/agronomy12010028
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Derived Smoke Ameliorates Salt Stress in Wheat by Enhancing Expressions of Stress-Responsive Genes and Antioxidant Enzymatic Activity

Abstract: Abiotic stresses are the biggest threat to the increasing population worldwide. Salt stress is one of the most significant abiotic stresses, affecting 20% of the crop production around the world. Plant-derived smoke (PDS) has been reported as a biologically active plant product in stimulating seed germination, seedling growth and physiological characteristics of crops under abiotic stress conditions. Nevertheless, studies showing how PDS alleviates salt stress are largely unknown. Here, we report the molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 64 publications
2
17
0
1
Order By: Relevance
“…Likewise, the majority of biochemical and physiological processes also get disturbed because of toxicity [ 48 , 49 , 50 , 51 ]. Recently, various concentrations of PDS have been used to restore plant growth under salt stresses; however, of these concentrations, PDS (2000 ppm) was found to most significantly alleviate the negative effect of salt stress [ 43 ]. Looking at the previous findings with PDS 2000 ppm, in the present study, we used PDS 2000 ppm to counteract the inhibitory effects of As and Hg stress, which is considered an ultimatum to the environment.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Likewise, the majority of biochemical and physiological processes also get disturbed because of toxicity [ 48 , 49 , 50 , 51 ]. Recently, various concentrations of PDS have been used to restore plant growth under salt stresses; however, of these concentrations, PDS (2000 ppm) was found to most significantly alleviate the negative effect of salt stress [ 43 ]. Looking at the previous findings with PDS 2000 ppm, in the present study, we used PDS 2000 ppm to counteract the inhibitory effects of As and Hg stress, which is considered an ultimatum to the environment.…”
Section: Resultsmentioning
confidence: 99%
“…A detailed study regarding the mitigatory role of PDS on the alleviation of negative effects of abiotic and heavy metal stress indicated that PDS plays a significant role in enhancing plant growth under heavy metal stress (Shabbir and Ilyas 2019, book chapter). Recently, PDS has been reported to mitigate the toxic effects of salt stress in wheat germination, seedling growth, and seedling fresh biomass [ 43 ]. Another study determined the well-proven alleviation effects of PDS on salt stress and improved the seed germination rate in maize [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations